(3GdCbQGHGPjfs - (3eMeO Hf HgQGe Hf eMeO GdbdGfSj GdSeQbfOj, HOQGdOjf , J (B590 (3g` s ((3jhSa Hf eMehO s)
(3ChdgG (B:s
(3jHOC GdehLhO efg HGdHGH GdChd aj PcQ GdNhGU CYde Cf GdCOhjI HYVgG fHGJjI hHYVgG eYOfjI hHYVgG MjhGfjI hGdeYOfjI haVdgG eG cGf ef GdeYGOf HgG eKd GdbdbOjS s
(3BNQgG (B:s
(3bGd GHhYHO Hf LHQjd aj efJNHGJg(B: (3ef WHGFY GdMjhGf hNhGUgG hbO LQH gPG aUM hjbdd GdScQ LOkG, hGddg JYGdi CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B122s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B29 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs